More on Generalizations and Modifications of Iterative Methods for Solving Large Sparse Indefinite Linear Systems - Jen-Yuan Chen; David R. Kincaid; Yu-Chien Li (Journal of Applied Mathematics)
Continuing from the works of Li et al. (2014), Li (2007), and Kincaid et al. (2000), we present more generalizations and modifications of iterative methods for solving large sparse symmetric and nonsymmetric indefinite systems of linear equations. We discuss a variety of iterative methods such as GMRES, MGMRES, MINRES, LQ-MINRES, QR MINRES, MMINRES, MGRES, and others.